2012
DOI: 10.5194/hessd-9-1345-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HESS Opinions "More efforts and scientific rigour are needed to attribute trends in flood time series"

Abstract: The question whether the magnitude and frequency of floods have changed due to climate change or other drivers of change is of high interest. The number of flood trend studies is rapidly rising. When changes are detected, many studies link the identified change to the underlying causes, i.e. they attribute the changes in flood behaviour to certain drivers of change. We propose a hypothesis testing framework for trend attribution which consists of essential ingredients for a sound attribution: proof of consiste… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 47 publications
(54 reference statements)
0
34
0
1
Order By: Relevance
“…While this study focused on the influence of temperature and precipitation changes on the observed streamflow increase, rigorous trend attribution studies should also comprise a search for possible alternative drivers and evidence that these are inconsistent with the observed changes [Merz et al, 2012]. Such alternative drivers could be changes in other meteorological variables than temperature or precipitation, in water management, or in land cover.…”
Section: Drivers Included In the Attributionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study focused on the influence of temperature and precipitation changes on the observed streamflow increase, rigorous trend attribution studies should also comprise a search for possible alternative drivers and evidence that these are inconsistent with the observed changes [Merz et al, 2012]. Such alternative drivers could be changes in other meteorological variables than temperature or precipitation, in water management, or in land cover.…”
Section: Drivers Included In the Attributionmentioning
confidence: 99%
“…The link between trends in streamflow and possible climatic drivers may be investigated by data-based or simulation-based approaches [Merz et al, 2012]. Data-based approaches directly relate changes in runoff to changes in climate without the additional step of applying a hydrological model.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies, which distinguish climate change and LULC impacts on historical trends in flood magnitude, but not systematically and within one modeling approach (e.g., [17]). To the best of our knowledge, the only study published which follows the protocol of Merz et al (2012) [5] is that by Hundecha and Merz (2012) [18]. Hundecha and Merz (2012) [18] drove a hydrological model with a large number of stationary and non-stationary climate time series in order to study whether the observed flood trend was climate driven.…”
Section: Introductionmentioning
confidence: 99%
“…The specific research question is, to which share LULC and/or climatic changes cause the increase of river flooding in the area. To this end, a simulation-based attribution approach proposed by Merz et al (2012) [5] is used. Merz et al (2012) [5] introduced a hypothesis testing framework for attributing changes of flood regime, which is based on testing the consistency or inconsistency of plausible drivers with the observed flood trend and providing a confidence level for the attribution.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand, analyze and model urban hydrology, as urbanization progression in West Africa is also the highest in the world, mostly due to the low current urbanization rate; • To improve the knowledge of the role of imperviousness and of drainage system; • To implement adapted hydrological modelling accounting for these processes and adopting rigorous statistical attribution approaches, as suggested, e.g., by Merz et al (2012) [119].…”
mentioning
confidence: 99%